(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article discusses the main changes made to the Law of the Republic of Uzbekistan "On the Securities Market," with a focus on the transformation of the Central Depository, the liberalization of the issuance of international bonds by residents, and the increase in information disclosure requirements. The prerequisites and objectives of legislative innovations, their potential impact on the country’s investment attractiveness, as well as the challenges associated with the implementation of these reforms, are considered. Special attention is paid to legal mechanisms ensuring transparency and protection of investors’ rights.